Adaptive Curriculum Development Based on Learning Analytics Analysis in Higher Education - Sumilat, Rohyani Rigen Is; Lee, Ava; Tan, Ethan; Purnomo, Widiharto (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2025)
The integration of learning analytics into higher education has the potential to revolutionize curriculum development by providing data-driven insights into student learning patterns, strengths, and weaknesses. Adaptive curriculum development, which tailors educational content to the diverse needs of students, is becoming increasingly important as educational institutions seek to improve student engagement, retention, and success rates. However, the effective implementation of adaptive curricula based on learning analytics remains underexplored in higher education contexts. This study aims to explore the potential of learning analytics in developing adaptive curricula that align with students’ learning behaviors, preferences, and academic performance. A mixed-methods approach was employed, combining quantitative data analysis of learning analytics with qualitative feedback from students and instructors. Data was collected from a cohort of 200 students enrolled in a large university, utilizing learning management systems to track student interactions, assessments, and engagement. The results indicate that curricula developed based on learning analytics led to significant improvements in student performance and engagement, particularly for at-risk students. Personalized learning paths and real-time adjustments were shown to enhance learning outcomes. This study concludes that learning analytics can play a crucial role in adaptive curriculum development in higher education, providing a pathway for more effective and personalized learning experiences.